How do you solve #6x + 3( 2- 3x ) = 3- 2( x - 1)#?

1 Answer
Jun 5, 2017

Answer:

#x = 1#

Explanation:

#6x + 3(2 - 3x) = 3 - 2 (x-1)#

We can solve this equation by isolating #x#.

We can first expand the brackets.

#6x + 6 - 9x = 3 - 2x + 2#

Now we can use algebra to isolate #x#

#6x - 9x = 3 - 2x + 2- 6#

#6x - 9x + 2x = 3 + 2- 6#

#6x - 9x + 2x = 5 - 6#

#6x - 9x + 2x = -1#

#- 3x + 2x = -1#

#- 1x = -1#

We cancel out the negative signs.

#cancel(-) 1x = cancel(-)1#

#1x = 1#

#color(blue)(x = 1#

Hope this helped :)